2001
DOI: 10.1097/00004424-200103000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Medium–Induced Pulmonary Vascular Hyperpermeability Is Aggravated in a Rat Climacterium Model

Abstract: These findings suggest that climacterium is included, at least in part, in the risk factors for contrast-induced adverse pulmonary reactions, and this risk is lowered by estrogen replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Furthermore, oestrogen and progesterone administration attenuated emphysematous and inflammatory changes in the lung as well as improved congestion and oedema following sepsis [ 87 ]. Tominaga et al showed that oophorectomized animals displayed a 2.6-fold increase in vascular permeability following ioxaglate treatment (a contrast medium that increases vascular permeability) compared to controls and that this effect was blocked following estradiol administration [ 106 ]. These effects may be secondary to the decreased expression of keratinocyte-derived chemokines (KDC), migration inhibitory factor (MIF) and TLR-4, which in turn reduces cytokine/chemokine production and neutrophil infiltration, reducing oedema formation and subsequent organ damage [ 107 , 108 ].…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, oestrogen and progesterone administration attenuated emphysematous and inflammatory changes in the lung as well as improved congestion and oedema following sepsis [ 87 ]. Tominaga et al showed that oophorectomized animals displayed a 2.6-fold increase in vascular permeability following ioxaglate treatment (a contrast medium that increases vascular permeability) compared to controls and that this effect was blocked following estradiol administration [ 106 ]. These effects may be secondary to the decreased expression of keratinocyte-derived chemokines (KDC), migration inhibitory factor (MIF) and TLR-4, which in turn reduces cytokine/chemokine production and neutrophil infiltration, reducing oedema formation and subsequent organ damage [ 107 , 108 ].…”
Section: Reviewmentioning
confidence: 99%
“…Experimental studies have shown that ioxaglate, which induced the largest increase in the PVR of the isolated rat lung preparation, is more cytotoxic to the vascular endothelium than diatrizoate and non-ionic contrast media (Table 1) (Benyon et al 1994;Zhang et al 2000;Emery et al 2001). Ioxaglate induced greater pulmonary edema in the rat than non-ionic monomeric contrast media (Mare et al 1984;Sendo et al 2000;Tominaga et al 2001). Interestingly, in the rat nitric oxide (Sendo et al 2000) and estrogen (Tominaga et al 2001) offered some protection against ioxaglate-induced pulmonary edema.…”
Section: Contrast Medium-induced Pulmonary Edemamentioning
confidence: 99%
“…Ioxaglate induced greater pulmonary edema in the rat than non-ionic monomeric contrast media (Mare et al 1984;Sendo et al 2000;Tominaga et al 2001). Interestingly, in the rat nitric oxide (Sendo et al 2000) and estrogen (Tominaga et al 2001) offered some protection against ioxaglate-induced pulmonary edema.…”
Section: Contrast Medium-induced Pulmonary Edemamentioning
confidence: 99%
“…At the seventh day after ovariectomy, rats were treated intramuscularly with either 17β-estradiol (1 mg/kg) or vehicle (sesame oil) once a week for three weeks, as described previously. 23 Measurement of extravasation of plasma protein in rat lungs. Plasma extravasation in lungs was evaluated, as described previously.…”
Section: Animals Male and Femalementioning
confidence: 99%